Rachunkowość zarządcza jako narzędzie zarządzania strategicznego w jednostkach samorządu terytorialnego - Rogus, Marlena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article introduces a management accounting as a toll of strategic management in of the local government administration. The management accounting should be an elementary and inseparable part of the strategic management. The main purpose of local government's administration is local evolution. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 349-358